MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK TENTANG SUHU DI SMP - Elma Shentya Fajarwati; Edy Tandililing; Syukran Mursyid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aimed to determine the effect of the quantum teaching model of the TANDUR framework on student learning outcomes in the temperature material of class VII SMP Negeri 6 Pontianak. The form of this research was in the form of quasi experimental design with the design of the nonequivalent control group design. The population used in this study were all Pontianak 6th Middle School students consisting of seven classes. While the samples taken consisted of two classes. Determination of the sample using intact group so as to obtain class VII A amounted to 25 people as the experimental class and class VII C amounted to 28 people as the control class. The data collection tool in this study included the pre-test and post-test tests in the form of 5 test questions. Based on the results of data analysis, the average score of the experimental class posttest 75.88 was higher than the control class 65. Based on the results of the Mann Whitney U-test, the sig value was obtained. 0,000> 0.05, then Ha is accepted so that there are differences in temperature learning outcomes between students using the quantum teaching model TANDUR framework with conventional learning. An effect size value of 1.11 was obtained which showed that the quantum teaching model of the TANDUR framework was based on the learning outcomes of students in SMP Negeri 6 Pontiank. so that it could be applied in science learning. Keywords: Learning Outcomes, Quantum Teaching.